Mobile app for crowdsourcing - Vivian, Claresta (2018)
Task crowdsourcing is a new way to outsource task by distributing it to a large group of people in exchange of monetary reward. There are many benefits of task crowdsourcing, namely increase in efficiency and productivity and decrease in labour cost. The motivation of this project was due to a lack of easy to access task crowdsourcing platform in Singapore. This gave rise to the idea of developing a hybrid mobile app for task crowdsourcing. This mobile application connects people who have tasks to do and people who are willing to help them. Users can message each other, manage their tasks and give and view reviews. This application was developed with Ionic3 as the framework, Firebase as the backend server and Google Maps API. On top of that, this mobile application is built for both iOS and Android users.